Safety and Efficacy of Limited Laboratory Monitoring for Hepatitis C Treatment: A Blinded Clinical Trial in Rwanda. Issue 4 (4th February 2020) - Grant, Philip; Shumbusho, Fabienne; Van Nuil, Jennifer Ilo; Kateera, Fredrick; Mukherjee, Joia; Kabahizi, Jules; Ntaganda, Fabien; Nsanzimana, Sabin; Mbituyumuremyi, Aimable; Damascene, Makuza Jean; Muvunyi, Claude Mambo; Mukabatsinda, Constance; et al.
Abstract : Direct‐acting antivirals for hepatitis C virus (HCV) are highly effective and well‐tolerated. However, only a small percentage of HCV‐infected individuals globally have received therapy. Reducing the complexity of monitoring during HCV therapy, if shown to be safe, could facilitate greater access to HCV services, particularly in resource‐limited settings such as sub‐Saharan Africa. We enrolled a total of 300 patients who were chronically infected with genotype 4 HCV in Rwanda and treated them with fixed‐dose ledispasvir/sofosbuvir for 12 weeks. For 60 consecutive participants enrolled, we blinded the study clinician to on‐treatment laboratory results. We compared the efficacy, safety, and tolerability in those with blinded laboratory results to those with standard laboratory monitoring. Baseline characteristics among those with blinded laboratory values were comparable to those with standard monitoring. Among both groups, the median age was 63 years, and the median HCV viral load was 5.9 log (versus 64 years and 6.0 log, respectively). Sustained virologic response rates at 12 weeks after treatment completion were similar in those with blinded laboratories (87%) compared to those with standard laboratory monitoring (87%). There was no increase in adverse events in those with blinded laboratory results, and no participants discontinued the study medication because of an adverse event. Conclusion: On‐treatment laboratory monitoring did not improve patient outcomes in those treated with ledispasvir/sofosbuvir. Eliminating this monitoring in treatment programs in resource‐limited settings may facilitate and accelerate scale‐up of HCV therapy. Abstract : With DAA therapy for HCV‐infected individuals in Rwanda, eliminating on‐treatment laboratory monitoring was safe. There was no difference in safety, tolerability, or efficacy in those participants who did not receive on‐treatment monitoring than in those who did.